Livelihood decisions under the shadow of conflict in the Chittagong Hill Tracts of Bangladesh - Muhammad Badiuzzaman; John Cameron; Syed Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
We analyse rural household livelihood and children's school enrolment decisions in a post-conflict setting in the Chittagong Hill Tracts region of Bangladesh. The innovation of the paper lies in the fact that we employ information about current subjective perceptions regarding the possibility of violence in the future and past actual experiences of violence to explain household economic decision-making. Preferences are endogenous in line with behavioural economics. Regression results show that heightened subjective perceptions of future violence and past actual experiences of conflict influences current consumption increases child enrolment, and encourages risky mixed crop cultivation. The trauma emanating from past experiences combined with current high perceptions of risk of violence may induce bolder and riskier behaviour in line with prospect theories of risk. Furthermore, a post-conflict household-level Phoenix or economic revival factor may be in operation, based in part on greater within group trust.
Keywords: D13; D72; D74; O13; 330; perceptions of violence; conflict; risk; post-conflict livelihood decision-making